Perancangan sistem informasi sekolah berbasis web pada TK Aisyiyah Bustanul Athfal 1 Bengkulu - Farhan, Farhan Suryadicka; Aspriyono, Hari; Al Akbar , Abdussalam (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
TK Aisyiyah Bustanul Athfal 1 Bengkulu is an early childhood education institution that still manages administrative and academic processes manually, such as recording student data, admitting new learners, and assessing learning outcomes. This has the potential to cause recording errors, data loss, and delays in information processing. This research aims to design a web-based school information system that can help manage school data and information in a computerized manner. The system includes student management, payment, assessment, and school profile modules. The methods used in designing this system include observation, interview, and literature study. System requirements analysis was conducted to identify the needs of users, both school managers and the community. The system was developed using Codeigniter 3 framework and MySQL database. It is expected that this system can improve the efficiency and accuracy of data management and accelerate the delivery of real-time information.